Surgical technique of endometrioma excision impacts on the ovarian reserve. Single-port access laparoscopy versus multiport access laparoscopy: a case control study. (June 2015) - Angioni, Stefano; Pontis, Alessandro; Cela, Vito; Sedda, Federica; Genazzani, Alessandro D.; Nappi, Luigi
Abstract Several recent studies report the detrimental effect of endometrioma excision on the ovarian reserve. Surgical technique and the excessive use of bipolar coagulation could be the key factors. Single-port access laparoscopy (SPAL) ovarian cystectomy has been reported as a comparable procedure to conventional laparoscopy in terms of operative outcomes. The aim of this study was to evaluate whether the single-port surgery affects the ovarian reserve whilst performing laparoscopic ovarian cystectomy for unilateral endometrioma. This was a prospective, case-control study of 99 women with unilateral endometrioma. Forty-nine women underwent single-port cystectomy and 50 women underwent multiport laparoscopic (MPL) conventional cystectomy. The primary outcome was the assessment of the ovarian reserve. We evaluated the serum anti-Mullerian hormone (AMH) levels before, 4–6 weeks and 3 months after surgery. At T2 we performed an ultrasound assessment of the antral follicular count (AFC). We have drawn attention to a statistically significant decrease of the mean AMH value and AFC in the SPAL group at the 4–6-week and 3-month follow-up compared to the conventional laparoscopy group. In conclusion, our results suggest that SPAL cystectomy should not be recommended to patients undergoing surgery for endometrioma excision who want to preserve their fertility.